Effect of restoring sinus rhythm in hypertensive patients with atrial fibrillation undergoing electrical cardioversion. Issue 6 (December 2016) - Maselli, Monica; Giantin, Valter; Franchin, Alessandro; Attanasio, Francesca; Tramontano, Alessandra; De Toni, Pietro; Pengo, Valentina; Corrado, Domenico; Manzato, Enzo
Abstract : Introduction: Little is known about the effects of atrial fibrillation (AF) on blood pressure (BP) levels in hypertensive patients. Some studies suggest a role for rhythm control in managing such patients' BP, but the improvement observed in cardiac performance after restoring sinus rhythm (SR) may coincide with an increase in BP. The aim of this study was to apply ambulatory BP monitoring to analyze BP changes in hypertensive patients after electrical cardioversion for persistent AF. Methods and results: The study included 54 hypertensive patients with persistent AF. Ambulatory BP monitoring was performed on the day before electrical cardioversion and again about a month later under conditions of stable medical treatment. Patients with a SR at follow-up ( n =34) had significantly higher 24-h, night-time ( P <0.05), and daytime ( P =0.074) systolic BP, and significantly lower 24-h, daytime ( P <0.05), and night-time ( P =0.078) DBP. The number of patients with nocturnal dipping decreased from 20 to 14 and the number of those with reverse dipping increased from 1 to 7. Patients with recurrent AF at follow-up ( n =20) showed no significant BP changes, except for a decrease in the mean night-time DBP. Conclusion: Restoring SR in hypertensive patients with AF led to a significant increase in their systolic BP (especially at night) and a decrease in their DBP. Hypertensive patients with AF should consequently undergo ambulatory BP monitoring after electrical cardioversion for the purpose of adjusting their antihypertensive treatment.